A new phase modulated binomial‐like selective‐inversion sequence for solvent signal suppression in NMR. (22nd September 2016) - Chen, Johnny; Zheng, Gang; Price, William S.
Abstract : A new8 ‐pulseP haseM odulated binomial‐like selective inversion pulse sequence, dubbed '8PM', was developed by optimizing the nutation and phase angles of the constituent radio‐frequency pulses so that the inversion profile resembled a target profile. Suppression profiles were obtained for both the 8PM and W5 based excitation sculpting sequences with equal inter‐pulse delays. Significant distortions were observed in both profiles because of the offset effect of the radio frequency pulses. These distortions were successfully reduced by adjusting the inter‐pulse delays. With adjusted inter‐pulse delays, the 8PM and W5 based excitation sculpting sequences were tested on an aqueous lysozyme solution. The 8 PM based sequence provided higher suppression selectivity than the W5 based sequence. Two‐dimensional nuclear Overhauser effect spectroscopy experiments were also performed on the lysozyme sample with 8PM and W5 based water signal suppression. The 8PM based suppression provided a spectrum with significantly increased ( doubled) cross‐peak intensity around the suppressed water resonance compared to the W5 based suppression. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new 8‐pulse Phase Modulated binomial‐like selective inversion sequence was developed for solvent signal suppression. The 8PM based excitation sculpting sequence provided higher suppression selectivity than the W5 based sequence. Twodimensional nuclear Overhauser effect spectroscopy experiments were performed on a lysozyme sample with 8PM and W5 based water signal suppression. The 8PM based suppression provided a significant intensity enhancement of the cross‐peaks around the water resonance.